Comparison of the Learning Outcomes in the Ecology Course Using Socio-Scientific Problem based Learning and Stimulus Environment Problem Solving Models - Kusumadani, Annur Indra; Nabila , Albertha Fausta; Najwa, Nadhifa (Journal of Biology Learning, 2025)
Learning that is still dominated by teacher-centered approaches tends to result in passive student participation and low learning outcomes. This study aims to compare the effectiveness of the Socio-Scientific Problem-Based Learning (SSPBL) model and the Stimulus Environment Problem Solving (SEPS) model in improving student learning outcomes in the Ecology course. The research employed a quasi-experimental design involving two groups of fourth-semester Biology Education students at Universitas Muhammadiyah Surakarta in the even semester of the 2023/2024 academic year. Each group consisted of 20 students; one was taught using the SSPBL model, and the other using the SEPS model. Data were analyzed using the independent sample t-test and effect size analysis.The results showed that the SSPBL group achieved significantly higher cognitive learning outcomes than the SEPS group in both Cycle I (sig. = 0.041) and Cycle II (sig. = 0.049). The effect size results further confirmed the high effectiveness of the SSPBL model, with values of 2.846 (Cycle I) and 3.413 (Cycle II), categorized as "high." These findings indicate that the SSPBL model is more effective in improving learning outcomes, particularly in developing higher-order thinking skills through the integration of scientific concepts and socio-scientific issues. This study recommends the implementation of the SSPBL model in science education to foster deeper conceptual understanding and critical thinking among students.